COMBINATION OF ANNONA MURICATA LINN SEED AND CLOVE (SYZYGIUM AROMTICUM) SEED EXTRACT AS A BIOINECTICIDE AGAINST HOUSEHOLD COCKHOUSES (PERIPLANETA AMERICANA) - Novian Aldo; Syahnan Purba; Romalina, Romalina; Artia Diarina (International Journal of Social Science, 2021)
Plants that are potential sources of plant insecticides, one of which is soursop. The active component of soursop seeds is acetogenin, which is considered to be larvicidal, and the azitogenin it contains is also an insecticide, acaricide, antiparasitic, and bactericidal agent. Another alternative to plants that can be used as herbal insecticides, besides soursop fruit seeds, is the clove leaf, which contains essential oil chemicals such as eugenol and other ingredients traditionally used to control cockroaches. The aim of the study was to determine the effect of soursop seed and clove leaf extract as a bioinsecticide in the control of vector cockroaches. This type of study is a real experiment with a research sample of 288 cockroaches. The results of this study showed that the extract of soursop seeds and clove leaves at a concentration of 80% caused the death of 14 cockroaches. The effectiveness level of soursop seed extract and clove leaves in the fight against domestic cockroaches is 80% concentration.